2021
DOI: 10.3390/ani11102810
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations and Haplotypic Diversity in the Myostatin Gene of Different Cattle Breeds in Russia

Abstract: The myostatin gene (MSTN) in cattle has a number of polymorphisms associated with increased muscle mass. The aim of the current study was to determine the haplotype frequencies of F94L and nt821(del11) MSTN polymorphisms among cattle bred for meat in Russia, using DNA analysis. Using the earlier created test systems based on the AS-PCR and PCR-RFLP methods, six populations of Aberdeen Angus (n = 684), two populations of Limousin (n = 54), one population of Simmental (n = 55), and one population of Belgian Blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…While the nt821 deletion is almost fixed in the Belgian Blue population ( Smith et al, 2000 ; Konovalova et al, 2021a ), it has been introduced in other breeds at a low frequency ( Gill et al, 2009 ; Konovalova et al, 2021b ). Because the haplotype with the nt821 deletion and the nt374_51 mutation was detected at a low frequency in the Angus population but was common in the Belgian Blue population, it is likely that the nt821 deletion was introduced into the Angus population through crossbreeding prior to 2003; the oldest Angus animal in the present study with that haplotype was born in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…While the nt821 deletion is almost fixed in the Belgian Blue population ( Smith et al, 2000 ; Konovalova et al, 2021a ), it has been introduced in other breeds at a low frequency ( Gill et al, 2009 ; Konovalova et al, 2021b ). Because the haplotype with the nt821 deletion and the nt374_51 mutation was detected at a low frequency in the Angus population but was common in the Belgian Blue population, it is likely that the nt821 deletion was introduced into the Angus population through crossbreeding prior to 2003; the oldest Angus animal in the present study with that haplotype was born in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Its codes region spans 1,128 nucleotides, resulting in a protein length of 375 amino acids [10]. Among these genes, the myostatin gene regulates muscle development and growth traits [11]. Previous studies have identified two mutations in the MSTN gene on exon 1, namely SNPc.111G>C (rs523392653) and SNP.267G>A (rs383271508) [10].…”
Section: Introductionmentioning
confidence: 99%
“…MSTN deactivation by genetic deletion or natural mutation causes muscle hypertrophy, which is widely reported in a variety of mammals [ 2 , 3 , 4 , 5 ]. In cattle breeding, MSTN has been a major subject research topic as a potential target for improving growth and production traits [ 6 , 7 , 8 ]. Using biological breeding technology, we conducted site-specific gene editing inactivation of MSTN by CRISPR/Cas9, effectively reduced the expression of MSTN, produced the purebred MSTN knockout Luxi cattle, which stably inherited the double muscle phenotype caused by MSTN deletion, forming a new breeding strain [ 9 ].…”
Section: Introductionmentioning
confidence: 99%